Optimum Lamina Configuration of I Glulam Beam - Johannes A Tjondro; Buen Sian (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
The I glulam beam may have several failure modes, such as failure in bending, wood shear, glue shear or adhesive between glue and wood. This paper presented the analitycal and experimental study of the optimum lamina configuration and dimension. The analytical results of achieving the optimum strength of I beam cross section with the same specific gravity of web and flange showed that the longer the span the smaller the web to flange width ratio needs. The I beam was not optimum when the cross section has a small ratio of span to beam height, the failure mode will be in wood shear. The contribution of sheardeflection was small at span to beam height ratio more than 20. The 12 specimens of I glulam beam made from Acacia mangium as web with flange variation using A. mangium, Meranti and Keruing. The wood specific gravity ratio of flange to web and the shear strength of glue were significant to make the wood and glue achieved the maximum strength. The oilly surface of Keruing flange made the load carrying capacity become low because of the wood-glue adhesive failure.Key words: deformation, failure mode, lamina configuration, flexural, shear, strength.